2018
DOI: 10.4236/ojped.2018.83025
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Non-Adherence to Antiretroviral Therapy among HIV-Infected Adolescents at Pediatric Department of Yopougon University Hospital, Côte d’Ivoire

Abstract: Context: The consequences of non-adherence to antiretroviral therapy (ART) are harmful in terms of morbidity and mortality among HIV-infected adolescents. There is a little data in this population in West Africa, about

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Makadzange et al, in Zimbabwe in 2012 in a study involving 418 adolescents reported a 33% rate of virologic failure among ALHIV on ART [ 14 ]. Similarly, alarming rates of VF have been reported among ALHIV, ranging from 34.2% (n = 92/270) in Cameroon in 2019, 41.8% (n = 69/165) in Côte d’Ivoire in 2017 to 51.6% (n = 86/167) in Togo in 2014 [ 15 , 21 , 22 ]. However, the distribution of VF was very heterogeneous, and varied from one health facility to another.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Makadzange et al, in Zimbabwe in 2012 in a study involving 418 adolescents reported a 33% rate of virologic failure among ALHIV on ART [ 14 ]. Similarly, alarming rates of VF have been reported among ALHIV, ranging from 34.2% (n = 92/270) in Cameroon in 2019, 41.8% (n = 69/165) in Côte d’Ivoire in 2017 to 51.6% (n = 86/167) in Togo in 2014 [ 15 , 21 , 22 ]. However, the distribution of VF was very heterogeneous, and varied from one health facility to another.…”
Section: Discussionmentioning
confidence: 99%
“…The median age of ART duration in our study was 7 years, suggesting significant exposure to first-line regimens based on reverse transcriptase inhibitor with a low genetic barrier. Sub-optimal adherence to ART is often associated with VF in children and adolescents on ART [ 22 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the task requires careful assessment of the status of adherence and age specific factors. 21 Studies on adherence to ART and associated factors among children below 15 years of age are limited in Ethiopia, in general and in the study area. Additionally, adherence is not static and can vary with time on treatment, making assessing adherence status crucial.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the authors are interested in the factors explaining the variations in prevalence from one region to another in Côte d'Ivoire (Essis et al, 2022) or the factors linked to the transmission of HIV between the infected mother and the new born (N'guessan et al, 2017). Other work focuses on the low adherence of adolescents to Anti-Retroviral (ARV) treatments among young people (Eboua et al, 2018). In the professional environment, the work deals with the mixed contribution of companies to the fight against the pandemic (Bekelynck, 2014) which could be explained by the constraints suffered by them due to deaths and also the lack of care appropriate for Workers Living with HIV (PLHIV) (Aventin, 1998).…”
Section: Introductionmentioning
confidence: 99%